The Problem of Orientation of Development Merdeka Belajar Curriculum - Belia, Stavini; Lubis, Jessyca Tania; Aprina, Serly; Nurfaiza, Nurfaiza; Illahi, Rahmat; Utama, Nanda Putra (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
The independent curriculum is a curriculum with various intra-curricular learning so that students are more optimal and have concepts and strengthen their competencies. The approach in this study uses a qualitative approach. Analysis of this research data using descriptive analysis. In this analysis, the data is interpreted descriptively and presented in a narrative manner. The results of the study revealed several problems found when implementing the 2022 independent curriculum in the two schools. In this independent curriculum, teachers are required to be more creative in designing teaching modules, learning objectives and the flow of learning objectives so that a teacher can no longer be careless in making lesson plans to design teaching and learning activities every week. The purpose of school work is only to strengthen the profile of Pancasila students. PS is still given to students every day but not only in class learning. Learning also needs to be carried out outside the classroom in order to increase the activity of students and innovate themselves